Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(x-y\right)^2\left(z^2-2z+1\right)-2\left(z-1\right)\left(x-y\right)^2+\left(x-y\right)^2\)
\(A=\left(x-y\right)^2\left(z-1\right)^2-2\left(x-y\right)\left(z-1\right)\left(x-y\right)+\left(x-y\right)^2\)
\(A=\left[\left(x-y\right)\left(z-1\right)-\left(x-y\right)\right]^2\ge0\) \(\forall x,y,z\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có:
\(\left(a+b\right)\left(a+c\right)+\left(c+a\right)\left(c+b\right)\)
\(=a^2+ac+ab+bc+c^2+bc+ac+ab\)
\(=a^2+c^2+2ac+2bc+2ab\)
Thay \(a^2+c^2=2b^2\) vào biểu thức ta được:
\(=2b^2+2ac+2bc+2ab\)
\(=2\left(b^2+ac+bc+ab\right)\)
\(=2\left[\left(b^2+bc\right)+\left(ac+ab\right)\right]\)
\(=2\left[b\left(b+c\right)+a\left(c+b\right)\right]\)
\(=2\left(b+a\right)\left(b+c\right)\)
\(\RightarrowĐpcm\)
\(0< =2\left|a\right|\cdot\left|b\right|\)
\(\Leftrightarrow\left(\left|a\right|\right)^2+2\cdot\left|a\right|\cdot\left|b\right|+\left(\left|b\right|\right)^2>=\left(\left|a\right|\right)^2+\left|b\right|^2\)
\(\Leftrightarrow\left(\left|a+b\right|\right)^2< =\left(\left|a\right|+\left|b\right|\right)^2\)
=>|a+b|<=|a|+|b|